Produção de biomassa de diferentes coberturas: o aporte de matéria orgânica e as alterações causadas nos atributos do solo - Mazetto Júnior, José Carlos (2018)
In the last 50 years, since its introduction in the 1970s in Brazil as a soil conservation system, the no-tillage system was consolidated as one of the most modern systems of sustainable agricultural production in brazilian cerrado, since no soil mobilization, maintenance of crop residues on the soil surface and an efficient system of crop rotation caused positive changes in the physical, chemical and biological attributes of the Latosols of the cerrado. The objective of this study was to evaluate the use of cover crops e quantify the changes caused in the physical attributes and soil organic matter, in irrigated area with conventional sprinkler irrigation. The work was developed in an experimental area of the Instituto Federal do Triângulo Mineiro (IFTM), Campus Uberaba-MG. Was adopted the completely randomized block design, with seven soil covers: 1 - brachiaria (B) (Urochloa brizantha cv. marandú), 2- crotalaria (C) (Crotalaria juncea), 3- millet ADR 500 (M) (Pennisetum glaucum L.), 4- B + C, 5- B + M, 6- C + M, with 3 repetitions. In addition, soil samples were collected under native forest, characterizing an additional treatment. Were evaluated the biomass production, the residues decomposition rate, the total organic carbon, soil organic matter coefficient and its fractionation (Humic Acid, Fulvic Acid and Humin). Were also evaluated the soil physical attributes: Bulk Density BD), Macroporosity (Ma), Microporosity (Mi), Total Porosity (TP), the Soil Aggregation (MWD, GMD and AEI), the Penetration Resistance (PR) and Volumetric Moisture (VM). The depths considered ranged from 0 to 60 cm, differing according to the attribute. he treatment with millet + crotalaria showed the highest values of total organic carbon and coefficient of organic matter in the depth up to 5 cm. Regarding the evaluated attributes, the millet was the cover plant that presented the best results. Brachiaria + millet was the best combination of cover crops to improve soil physical quality in depth.